Preliminary Studies on Magnetite/Cdots Nanocomposite: Structure, Functional Compound, and Morphology - Bian Itsna Ashfa Al Ashfiya; Ahmad Taufiq (JPSE (Journal of Physical Science and Engineering), 2024)
This research develops Fe₃O₄/Cdots nanocomposites as an effective heavy metal adsorbent in batik industrial waste. The batik industry produces waste with hazardous heavy metal content that requires efficient processing methods. Fe₃O₄ was chosen because of its magnetic properties that facilitate separation after adsorption, while Cdots have the ability to detect and adsorb heavy metal ions. Fe₃O₄/Cdots nanocomposites are synthesized through hydrothermal methods and coprecipitation with Cdots materials sourced from orange juice and Fe₃O₄ from natural iron sand. XRD analysis confirmed the formation of the crystalline structure of Fe₃O₄ and the amorphous phase of Cdots, which are important for magnetic properties and adsorption. The FTIR spectrum shows the presence of functional groups that support interactions with metal ions. SEM test results showed particle sizes ranging from 35–65 nm, while EDX data confirmed the dominant composition of Fe₃O₄ and Cdots. This nanocomposite offers the potential as an efficient and magnetically separable batik waste treatment solution.